(untitled) (Revista de Estudos da Linguagem, 1999)
This paper presents a partial analysis of the use of the item onde (where)in academic written texts produced by university students. These textstend to present several cohesive mechanisms which are responsiblefor their realability. In general, the author constructs a coherentand cohesive discourse in order to lead his/her reader to the desiredmeaning. Nevertheless, sometimes he/she fails in using cohesivemechanisms, and that leads to a local incoherence, according toCharolles (1988). One example is the use of onde in written texts.In these texts, several passages were found in which this word wasused without reference to places, i.e. not according to what isprescribed by traditional Portuguese grammar. It seems that thisuse of onde points to a different function, an enlargement of itsfield of action.